2013
DOI: 10.1136/bjophthalmol-2012-303043
|View full text |Cite
|
Sign up to set email alerts
|

In vivo optical coherence tomography (OCT) in periocular basal cell carcinoma: correlations between in vivo OCT images and postoperative histology

Abstract: This study indicated a strong positive correlation between the margins of periocular BCCs measured using in vivo OCT and histology, and a weak positive correlation with depth of invasion. VivoSight OCT produced high resolution images of BCC morphology. The limitations in horizontal margin measurements could potentially be overcome by design modification of the scanning probe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 21 publications
2
28
0
1
Order By: Relevance
“…Recent HD-OCT studies using Skyntell (Agfa) observed similar BCC diagnostic features in agreement with previous publications 11,17,18 including dark lobulated nodules, peripheral rimming, peritumoral bright stroma and dilated blood vessels. Interestingly, the detection of lobulated nodules (84 vs 40%), peritumoral bright stroma (88 vs 68%) and dark peripheral rimming (72 vs 32%) appeared to be consistently higher in HD-OCT en-face images compared to slice mode scans.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Recent HD-OCT studies using Skyntell (Agfa) observed similar BCC diagnostic features in agreement with previous publications 11,17,18 including dark lobulated nodules, peripheral rimming, peritumoral bright stroma and dilated blood vessels. Interestingly, the detection of lobulated nodules (84 vs 40%), peritumoral bright stroma (88 vs 68%) and dark peripheral rimming (72 vs 32%) appeared to be consistently higher in HD-OCT en-face images compared to slice mode scans.…”
Section: Discussionsupporting
confidence: 74%
“…[14][15][16] The original OCT diagnostic criteria for BCC lesions were described by Olmedo et al using conventional OCT. 11 In our study, Fourier domain imaging showed dark lobular patterns of BCC nests and bright margins of collagen compression in 100%; decreased reflectance at the borders of the lobules was seen in 73% of the lesions, whereas dilated blood vessels were detected in only 33%, in keeping with previous studies. 15,18 The additional feature of central necrosis was observed in 20% of lesions and suggested the BCC growth pattern with fast progressive enlargement outgrowing the tissue blood supply.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraoperative OCT can provide both qualitative and quantitative three-dimensional information. A recent study utilized OCT in many surgical specialties, especially in ophthalmology imaging (Joos and Shen, 2013; LaRocca et al, 2013; Lu et al, 2014; Lucia Pelosini, 2013; Paul Hahn, 2011; Ramiro S. Maldonado, 2010; Tao et al, 2010; Woonggyu Jung, 2012) and coronary imaging (Bouma and Tearney, 1999; Ferrante, 2013; Jang et al, 2002). Intraoperative evaluation of breast tumor margins using OCT has also been reported (Nguyen, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The difference between OCT and reflectance confocal microscopy is the ability of OCT to image to a depth of 1 mm; however, this increased penetration depth comes at the cost of reduced resolution. Ultimately, of course, this method also aims at reducing the need for invasive biopsies by providing reliable images that allow for diagnostic decisions and for treatment response monitoring [16][17][18].…”
Section: Fortschritte In Der Dermatologiementioning
confidence: 99%